Cricoid Chondrosarcoma Presenting as Breathy Dysphonia - Baranwal, C; KC, T; Bista, M; Regmi, D (Nepalese Journal of ENT Head and Neck Surgery, 2013)
Nepalese Journal of ENT Head and Neck Surgery, Vol. 3 Issue 1 (Jan-June 2012) Page 13-14 DOI: http://dx.doi.org/10.3126/njenthns.v3i1.8182